Pengaruh Trust, Price dan Service Quality Terhadap Repurchase Intention Pada UD. Ananda Di Masbagik Lombok Timur - Rima Shobrina; Zulkarnaen; Surahman Hidayat (Kredibel: Jurnal Ilmiah Manajemen, 2023)
This research aims to determine the influence of Trust, Price, and Service Quality on Repurchase Intention at UD. Ananda Wholesale in Masbagik, East Lombok. The data analysis technique used is multiple linear regression analysis technique with results Y = 1,464 + 0,117X1 + 0,407X2 + 0,288X3 calculated using the SPSS 25 program. Based on the results of the multiple linear regression test, it can be concluded that the constant value is 1.464, meaning that if there is no change in the trust, price and service quality variables (the values ​​of X1, X2 and X3 are 0). So, repurchase intention at UD. Ananda Wholesale amounted to 1,464 units. The results of this research also show that the t test (partial) states that the trust variable is not significant, the price variable has a significant effect, the service quality variable has an insignificant effect. Based on the F test (simultaneous), it states that the variables trust, price and service quality simultaneously influence repurchase intention and the beta test shows that the variable has a dominant influence on repurchase intention at UD. Ananda Wholesale is the price variable.